2010
DOI: 10.4269/ajtmh.2010.09-0629
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Validated Peripheral Neuropathy Screening Tool in Patients Receiving Antiretroviral Therapy in Mombasa, Kenya

Abstract: Abstract. Limited objective data are available for the prevalence of peripheral neuropathy (PN) among antiretroviral (ART)-treated human immunodeficiency virus (HIV)-infected patients in resource-limited settings. A validated neuropathy-screening tool was integrated into routine ART visits at an HIV clinic in Mombasa, Kenya. Diagnosis of PN required at least one symptom and either abnormal vibratory sensation or deep tendon reflex bilaterally. Among 102 consecutively screened patients, 63% were women, 62% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 13 publications
4
39
2
Order By: Relevance
“…This was the case in 19.7% (58/295) of our study population. Some authors [19,20] considered this group as asymptomatic PN who perhaps represent those with early HIV-SN who are more likely to become symptomatic when challenged with HAART or other risks for PN [20]. Considering together those with HIV-SN (according to BPNS criteria) as symptomatic PN patients and those with clinical abnormalities relevant with PN but no symptoms as asymptomatic PN patients, increases the prevalence of PN in our study to 40.7%.…”
Section: Discussionmentioning
confidence: 75%
“…This was the case in 19.7% (58/295) of our study population. Some authors [19,20] considered this group as asymptomatic PN who perhaps represent those with early HIV-SN who are more likely to become symptomatic when challenged with HAART or other risks for PN [20]. Considering together those with HIV-SN (according to BPNS criteria) as symptomatic PN patients and those with clinical abnormalities relevant with PN but no symptoms as asymptomatic PN patients, increases the prevalence of PN in our study to 40.7%.…”
Section: Discussionmentioning
confidence: 75%
“…Some authors considered this group as asymptomatic PN who perhaps represent those with early HIV-SN who are more likely to become symptomatic when challenged with HAART or other risks for PN. [16,17] Subclinical neuropathy in our study was 16% using NCS. According to Skopelitis and collaborators who used a model involving both clinical criteria and electrophysiological studies, two-thirds of HIV-SN is subclinical.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of HIV-SN in our study population was 40% though, varying greatly among different studies between 19 and 42%. [13][14][15][16][17][18][19] Evans et al, reported the prevalence of neuropathy in pre-HAART patient to be 26.90%. [17] Cherry et al, reported 42% prevalence of HIV neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were asked at each 12-weekly visit of any symptoms consistent with peripheral neuropathy, which were then graded by the doctor taking into consideration other causes based on a physical examination conducted at each visit; thus, our outcome is based on self-report in contrast to other studies such as the BPNS used in Mehta et al [11], which incorporated objective measures as well as reported symptoms. Estimates of prevalence and incidence will depend on the criteria used to define peripheral neuropathy; nevertheless, the fact that we found the expected predictors of pre-ART age, weight and stavudine use suggests that this outcome was reasonably well ascertained.…”
Section: Aids 2014 Vol 28 No 17mentioning
confidence: 99%
“…However, these tools have been less frequently used in resource-limited settings. The few existing studies in sub-Saharan Africa have shown widely varying prevalence of 1-60% with HIV or ART-related peripheral neuropathy [7,[9][10][11][12][13][14][15]. The post-ART incidence rates for peripheral neuropathy were also not consistent across several studies, varying between 0.9 and 40 per 100 person-years in a review [15].…”
Section: Introductionmentioning
confidence: 96%